Morphological Disambiguator for Marathi using NLP (International Journal of Scientific Research and Management (IJSRM), 2015)
Natural Language Processing (NLP) is an emerging technology in recent years, which consist of Morphological analysis of languages. Morphological analysis gives description about words in that language. Morphological analysis of Indian languages is a difficult task. In an Indian language like Marathi word can have many inflections which results in ambiguity. So the description generated by analysis can be further used to find out the meaning of that word to remove ambiguity while translating from one language to another. This paper describes an approach for finding the meaning of the word, using description generated by the analysis and other information such as the position of the word in a sentence, suffix etc., to remove ambiguity when translating sentence written in Marathi (Devnagari) language to English language.